Ecological Effects of Sargassum fusiforme Cultivation on Coastal Phytoplankton Community Structure and Water Quality: A Study Based on Microscopic Analysis - Yurong Zhang; Rijin Jiang; Qingxi Han; Zimeng Li; Zhen Mao; Haifeng Jiao (Biology, 2025)
This study used microscopy-based quantitative enumeration to investigate the effects of large-scale Sargassum fusiforme cultivation on coastal water quality and phytoplankton communities. Data from April (cultivation period) and June (non-cultivation period) in 2018 and 2019 showed that cultivation increased pH and dissolved oxygen (DO). It also reduced nitrate–nitrogen (NO3–N), nitrite–nitrogen (NO2–N), phosphate–phosphorus (PO4–P), total phosphorus (TP), and silicate–silicon (SiO3–Si) concentrations. These changes indicate improved coastal water quality from S. fusiforme cultivation. Nutrient levels rose again during the non-cultivation period. This suggests that water purification decreased without cultivation. Cultivation also lowered the dominance of Skeletonema costatum. This led to a more diverse and stable phytoplankton community. Microscopic observation is valuable for quantifying larger phytoplankton species, and plays an important role in ecological monitoring. These findings provide insights for sustainable aquaculture and ecological restoration.